Pengembangan Media Pembelajaran Game Petualangan Perkalian Matematika “GAPETIKA” untuk Siswa Sekolah Dasar - Latifatul Istiqomah; M. Yusuf Setia Wardana; Husni Wakhyudin (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2023)
The background of this research is because so far the teacher only uses learning methods such as the lecture method or only requires students to memorize, so students get bored and bored while learning. And the learning environment is not designed to facilitate student independent learning, and students have different speeds and methods according to their individual abilities. The purpose of this study is the development, validation and acceptance of a gapetic learning environment (games for further development of mathematics). The research and development method of the ADDIE development model is used as a research method. The research subjects were fourth grade students of SD Negeri Karangtengah 1. The results showed that the average score of the Material Validation Survey was 92%, the Media Validation Survey was 95%, the Student Response Survey was 100%, and the Teacher Response Survey was 93% which means very good. This proves that the learning environment for completing mathematics through adventure games can be used and is effective for fourth grade students at SD Negeri Karangtengah 1.